Enumerating a continental-scale threat: How many feral cats are in Australia?. (February 2017) - Legge, S.; Murphy, B.P.; McGregor, H.; Woinarski, J.C.Z.; Augusteyn, J.; Ballard, G.; Baseler, M.; Buckmaster, T.; Dickman, C.R.; Doherty, T.; Edwards, G.; Eyre, T.; et al.
Abstract: Feral cats ( Felis catus ) have devastated wildlife globally. In Australia, feral cats are implicated in most recent mammal extinctions and continue to threaten native species. Cat control is a high-profile priority for Australian policy, research and management. To develop the evidence-base to support this priority, we first review information on cat presence/absence on Australian islands and mainland cat-proof exclosures, finding that cats occur across >99.8% of Australia's land area. Next, we collate 91 site-based feral cat density estimates in Australia and examine the influence of environmental and geographic influences on density. We extrapolate from this analysis to estimate that the feral cat population in natural environments fluctuates between 1.4 million (95% confidence interval: 1.0–2.3 million) after continent-wide droughts, to 5.6 million (95% CI: 2.5–11 million) after extensive wet periods. We estimate another 0.7 million feral cats occur in Australia's highly modified environments (urban areas, rubbish dumps, intensive farms). Feral cat densities are higher on small islands than the mainland, but similar inside and outside conservation land. Mainland cats reach highest densities in arid/semi-arid areas after wet periods. Regional variation in cat densities corresponds closely with attrition rates for native mammal fauna. The overall population estimate for Australia's feral cats (in natural and highly modified environments), fluctuating between 2.1 and 6.3 million, is lower than previous estimates, and Australian feral cat densities are lower than reported for North America and Europe. Nevertheless, cats inflict severe impacts on Australian fauna, reflecting the sensitivity of Australia's native species to cats and reinforcing that policy, research and management to reduce their impacts is critical. Highlights: A collation of 91 studies was used to estimate Australia's feral cat population. Feral cats are present on >> 99.8% of Australia's land area. Feral cat numbers in Australia fluctuate (2.1–6.3 million) with antecedent rainfall. Feral cat density is higher on small islands, and in arid/semi-arid areas after rain. Feral cat impacts on Australian biodiversity have been particularly severe. Graphical abstract: The population size of feral cats in natural environments in Australia fluctuates between 1.4 and 5.6 million, depending on rainfall. An additional 0.7 million feral cats live in heavily modified environments like towns and intensive farms. The maps show the model predictions for cat density in natural environments across Australia during dry-average rainfall conditions (on the left) and after extensive rainfall events (on the right). They show that cat density is fairly uniform across the continent during average-dry conditions, but extensive rainfall events cause an increase in feral cat density in the inland of Australia. As predictors, the regression model includes mean annual rainfall, mean annual temperature, tree cover, ruggedness and fox presence/absence. For islands smaller than Tasmania, island area was also included as a predictor of density (small islands have higher cat densities). The dashed lines indicate the Tropic of Capricorn.